Incident syphilis infection among people who inject drugs in Tijuana, Mexico. (December 2015) - Pines, Heather A; Rusch, Melanie L; Vera, Alicia; Rangel, Gudelia; Magis-Rodriguez, Carlos; Strathdee, Steffanie A
Summary: Given that syphilis is associated with HIV infection among people who inject drugs (PWID), we examined syphilis incidence among PWID in Tijuana, Mexico. From 2006 to 2007, 940 PWID (142 women and 798 men) were recruited via respondent-driven sampling and followed for 18 months. At semi-annual visits, participants were tested for syphilis and completed surveys, which collected information on socio-demographics, sexual behaviours, substance use and injection behaviours. Poisson regression was used to estimate syphilis incidence rates (IRs), incidence rate ratios (IRRs) and 95% confidence intervals (CIs). Twenty-one participants acquired syphilis during follow-up (IR = 1.57 per 100 person-years, 95% CI: 1.02–2.41). In a multivariate analysis, syphilis incidence was higher among women (IRR = 3.90, 95% CI: 1.37–11.09), HIV-positive participants (IRR = 4.60, 95% CI: 1.58–13.39) and those who reported ever exchanging sex for drugs, money, or other goods (IRR = 2.74, 95% CI: 0.97–7.76), while syphilis incidence was lower among those living in Tijuana for a longer duration (IRR = 0.95 per year, 95% CI: 0.91–1.00) and those reporting at least daily injection drug use (past 6 months) (IRR = 0.22, 95% CI: 0.09–0.54). Our findings suggest interventions that address the destabilising conditions associated with migration and integrate sexual and drug-related risk reduction strategies may help reduce syphilis incidence among PWID along the Mexico–US border.